不一樣的人生道路？STEM科系畢業生的薪資發展軌跡 Different Life Pathway: Earning Trajectory of the Graduates in STEM Majors - 張宜君 Yi-Chun Chang (臺灣教育社會學研究)
本研究企圖整合教育擴張後高等教育水平分化的系所效應及生命歷程軌跡框架，補充過去系所選擇研究多聚焦於性別議題或討論中學階段的「選擇進入」議題之不足，且在方法論上檢視過去橫斷面思考薪資報酬的限制。本研究將薪資取得過程中的不確定性、不可預測性及個人生命各面向的多樣性納入薪資軌跡，以生命歷程軌跡框架理解STEM科系的選擇對個人薪資軌跡發展的影響。本研究合併2009～2020年的華人家庭動態資料庫，以成長曲線模型捕捉STEM科系對薪資成長的影響，分析結果發現：STEM專業訓練勞動者的薪資顯著高於非STEM專業的勞動者，且其優勢隨著工作經驗累積而增加；但此優勢存在性別差異，女性展現在起薪優勢，而男性則是後勢看漲的優勢；更精確地說，STEM專業的薪資發展優勢僅存在於一般大學男性之間。此結果揭示STEM專業訓練與勞動市場後果之間的關係如何受教育制度及生命歷程影響，這些勞動市場的STEM優勢及性別化差異，也將進一步影響STEM人才培育及其階層化後果。 This study attempts to integrate the literature in the horizontal differentiation of higher education expansion and the life course trajectory framework. It supplements the shortcomings of past studies on STEM education that mostly focused on gender issues or the issues of probability of “entering” STEM in high school, and examines the methodological limitations of using cross-sectional data. In this study, the labor market uncertainty and unpredictability, and the diversity in all aspects of personal life, are incorporated into the life course trajectory. This study systematically investigates the influence of majoring in STEM fields on individual earning trajectory. Merging the Panel Study of Family Dynamics from 2009 to 2020 and using the growth curve model to estimate the effects of STEM education on earning trajectory, the findings show that the earnings of workers trained in STEM majors are significantly higher than those of workers in non-STEM majors, and their advantages increase with the accumulation of work experience. However, there are gender differences in this advantage. Women have a starting salary advantage, while men have advantages of salary accumulation. Precisely, these advantages of STEM majors in the earnings only exist among male academic-track college graduates. These results reveal how the educational system and life course affect the relationship between STEM education and labor market outcomes. These patterns of STEM advantages and gender differences in the labor market will further influence the cultivation of STEM professionals and the patterns of social stratification.